Pengaturan Sanksi Pidana terhadap Pengemplang Pajak Perspektif Kepastian Hukum - Paini; Lasmadi, Sahuri; Sudarti, Elly (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to analyze the regulation of criminal sanctions against tax evaders from the perspective of legal certainty and to formulate future criminal law policies that are more effective in protecting state revenue. This research employs a normative juridical method with conceptual, statutory, and case approaches, relying on primary, secondary, and tertiary legal materials analyzed through inventory, systematization, and interpretation techniques. The findings indicate that the regulation of criminal sanctions in Indonesian tax law still faces issues of normative ambiguity, particularly in distinguishing between administrative violations and criminal offenses, as well as the absence of explicit regulation on tax avoidance practices. Furthermore, the application of the ultimum remedium principle weakens the deterrent effect, as administrative settlements are prioritized over criminal enforcement. This condition results in suboptimal protection of state revenue and undermines legal certainty. Therefore, a reformulation of tax criminal law policy is necessary to clarify legal norms, strengthen the repressive function of criminal sanctions, and ensure consistent law enforcement to support fiscal stability.